2001
DOI: 10.1179/107735201800339470
|View full text |Cite
|
Sign up to set email alerts
|

Amyotrophic Lateral Sclerosis in a Battery-factory Worker Exposed to Cadmium

Abstract: A 44-year-old patient died from amyotrophic lateral sclerosis (ALS) after nine years of heavy exposure to cadmium (Cd) in a nickel cadmium (Ni-Cd) battery factory. Two years after starting work he and co-workers had experienced pruritus, loss of smell, nasal congestion, nosebleeds, cough, shortness of breath, severe headaches, bone pain, and proteinuria. Upper back pain and muscle weakness progressed to flaccid paralysis. EMG findings were consistent with motor neuron disease. Cd impairs the blood-brain barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 0 publications
2
38
0
1
Order By: Relevance
“…Metals have been studied for a long time in order to understand pathogenic mechanisms underlying development of neurodegenerative disease better, and to date there are prospects of study for this topic [71]. As for cadmium, apart from recent evidence of a high metal concentration in the cerebrospinal fluid of ALS patients [85], there are some works focusing on occupational exposures in certain employment sectors, such as production of nickel-cadmium batteries [86,87]. Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Metals have been studied for a long time in order to understand pathogenic mechanisms underlying development of neurodegenerative disease better, and to date there are prospects of study for this topic [71]. As for cadmium, apart from recent evidence of a high metal concentration in the cerebrospinal fluid of ALS patients [85], there are some works focusing on occupational exposures in certain employment sectors, such as production of nickel-cadmium batteries [86,87]. Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, Cd 2+ concentrations are significantly elevated in the brains of AD (Lui et al, 1990) and ALS (Vinceti et al, 1997) patients. Also, occupational exposure to Cd 2+ increases the risk of AD (Bar-Sela et al, 2001), ALS, and brain atrophy (Bar-Sela et al, 1992). Exposure to Cd 2+ can cause the development of parkinsonism three months after recovery from acute Cd 2+ toxicity (Okuda et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Cadmium is known as a potent toxic metal in industrial and food contamination, and it is harmful to human because it accumulates in liver, kidney, and other tissues. It has been reported that cadmium exposure causes ALS by reducing the superoxide dismutase activity [Bar-sela et al, 2001]. However, the mechanism of cadmium decrease the activity of Cu,Zn-SOD protein is not clear.…”
mentioning
confidence: 98%